Pengaruh Kualitas Produk, Lifestyle, Country Of Origin Terhadap Keputusan Pembelian - Cici Dwi Tamara; Ra Nurlinda (Lembaga Pengembangan Kinerja Dosen, 2024)
Currently,smartphone use is increasing and growing very rapidly. As a result of the increasing use of smartphones, entrepreneurs in the technology sector are increasingly racing and competing to increase their sales by releasing new products with sophisticated features and diverse and attractive models. The iPhone is one of the smartphones that is in great demand among various groups. The first appearance of the iPhone in the world began in 2007 and every year Apple continues to launch new products with increasingly developed specifications. This research examines the direct influence of product quality, lifestyle, country of origin on purchasing decisions. Primary data was collected using a survey method by distributing questionnaires to 160 respondents, the data was then processed using the path analysis method. Based on the results of the research analysis, there is a direct influence between product quality, lifestyle, country of origin on purchasing decisions.